Determination of the polymer-solvent interaction parameter for PEG hydrogels in water: Application of a self learning algorithm. (1st June 2015) - Akalp, Umut; Chu, Stanley; Skaalure, Stacey C.; Bryant, Stephanie J.; Doostan, Alireza; Vernerey, Franck J.
Abstract: Concentrating on the case of poly(ethylene glycol) hydrogels, this paper introduces a methodology that enables a natural integration between the development of a so-called mechanistic model and experimental data relating material's processing to response. In a nutshell, we develop a data-driven modeling component that is able to learn and indirectly infer its own parameters and structure by observing experimental data. Using this method, we investigate the relationship between processing conditions, microstructure and chemistry (cross-link density and polymer-solvent interactions) and response (swelling and elasticity) of non-degradable and degradable PEG hydrogels. We show that the method not only enables the determination of the polymer-solvent interaction parameter, but also it predicts that this parameter, among others, varies with processing conditions and degradation. The proposed methodology therefore offers a new approach that accounts for subtle changes in the hydrogel processing. Graphical abstract: Highlights: A self-learning framework is developed to assess the χ parameter in PEG hydrogels. The framework provides an indirect way to measure χ parameter. Stiffness and swelling are very sensitive to χ parameter. The effect of processing conditions and degradation on χ parameter is measured. The approach provides better understanding of the molecular physics of hydrogels.